2009
DOI: 10.1021/jm900080g
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Prodrugs of the Human Immunodeficiency Virus Protease Inhibitors Lopinavir and Ritonavir

Abstract: We studied the synthesis, cleavage rates, and oral administration of prodrugs of the HIV protease inhibitors (PIs) lopinavir and ritonavir. Phosphate esters attached directly to the central hydroxyl groups of these PIs did not demonstrate enzyme-mediated cleavage in vitro and did not provide measurable plasma levels of the parent drugs in vivo. However, oxymethylphosphate (OMP) and oxyethylphosphate (OEP) prodrugs provided improved rates of cleavage, high levels of aqueous solubility, and high plasma levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 17 publications
1
39
0
Order By: Relevance
“…Other authors have also reported different dephosphorylation rates depending on the prodrug (Heimbach et al, 2003a;DeGoey et al, 2009). Fosphenytoin has a methylene linker and shows the fastest turnover.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Other authors have also reported different dephosphorylation rates depending on the prodrug (Heimbach et al, 2003a;DeGoey et al, 2009). Fosphenytoin has a methylene linker and shows the fastest turnover.…”
Section: Discussionmentioning
confidence: 94%
“…Clindamycin is a direct prodrug and shows relatively slower turnover. Among the two ritonavir prodrugs, the candidate with a flexible oxymethyl linker cleaves while the direct phosphate shows no turnover, which could be due to the poor accessibility of the phosphate ester into the enzyme active site (DeGoey et al, 2009). The rank order (from slowest to fastest turnover) in rat rIALP was ritonavir oxymethyl phosphate, clindamycin phosphate, dexamethasone phosphate, and fosphenytoin, whereas in RIMS the rank order was clindamycin phosphate, ritonavir oxymethyl phosphate, dexamethasone phosphate, and fosphenytoin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the extraction of both, soluble phase and biomass, it could be observed that the highest amount of unconverted substrate remained in the biomass phase (10.4 mg). With a ritonavir solubility of 0.30 mg L −1 in water, precipitation of ritonavir and accumulation in the biomass is likely. The poor solubility makes high substrate loading challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, we turned to a synthetic scheme that had previously be used to synthesize OMP prodrugs, namely methylthiomethyl (MTM) ether formation followed by reaction with N‐iodosuccinimide (NIS) and a phosphate 22. 24, 25 We successfully synthesized the desired MTM ether intermediate 9 via a Pummerer rearrangement by stirring 4 in DMSO, acetic anhydride (Ac 2 O), and acetic acid (AcOH) (Scheme ). Unfortunately, treating 9 with NIS and either dibenzyl phosphate or H 3 PO 4 did not lead to any isolable product.…”
Section: Resultsmentioning
confidence: 99%